THE IMPACT OF FLURAL LIVING'S CONSUMPTION BEHAVIOR ON STATE REVENUE AFTER A 12% VAT INCREASE - Dillah Faradilla Hasanah; Nurlaila Syarifah Asfo; Andi Sutra Rimba; Andi Sumarlin K (CV. Radja Publika, 2026)
The increase in Value Added Tax (VAT) to 12% in Indonesia has had various impacts on people's consumption patterns, especially in the natural living lifestyle that reflects sustainable, experience-based, and digital consumption. This study aims to analyze the impact of the consumption behavior of natural living on state revenues following the VAT increase policy. A quantitative approach was used with a survey method of 500 respondents from five major cities in Indonesia. Primary data was collected through an online questionnaire, while secondary data was obtained from official government reports and related literature. The increase in Value Added Tax (VAT) to 12%, implemented in Indonesia in 2022, has triggered significant changes in consumer behavior, particularly in the Flural Living segment. This article aims to analyze the impact of Flural Living's consumer behavior on state revenue following the VAT increase. Utilizing statistical data and relevant case studies, this article will discuss how changes in consumer behavior can affect state revenue through increases or decreases in the consumption of goods and services. The analysis is expected to provide insights for policymakers in formulating more effective tax strategies. This study concludes that a sustainable living lifestyle is a potential source of increased state revenue from VAT. However, incentive policies to encourage sustainable consumption and public education to raise awareness of tax contributions are needed. These results are expected to provide input to the government in formulating a more inclusive tax strategy and supporting sustainable economic development.